INVENTORY TURNOVER SEBAGAI DETERMINAN RETURN ON ASSETS PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ajeng Intan Putri Nurhanifah; Sukadwilinda; Anggi Putri Kusuma Wardini; Muhammad Taofik Ismail (Universitas Sangga Buana, 2026)
Inventory management is an important aspect of improving corporate profitability, particularly in the Consumer Non-Cyclicals sector, where maintaining product availability is essential to meet stable market demand. This study aims to examine the effect of Inventory Turnover on Return on Assets (ROA) of IDX-IC Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employed a quantitative approach using secondary data obtained from annual financial reports. A total of 58 companies, representing 174 observations, were selected through purposive sampling. Data were analyzed using panel data regression with the Random Effect Model (REM). The findings indicate that Inventory Turnover has a negative and insignificant effect on ROA, with a probability value of 0.7636 (>0.05). These results suggest that inventory turnover is not the primary determinant of profitability in the Consumer Non-Cyclicals sector, indicating that other operational and financial factors play a more significant role in explaining corporate profitability